Organizing of pharmacokinetic investigations - I. I. Miroshnichenko; O. Y. Kravtsova (LLC "Publisher OKI", 2022)
The paper is devoted to various aspects of the organization of drug pharmacokinetics research both at the preclinical and clinical levels (bioequivalence study, therapeutic drug monitoring, optimization of dosage regimens), as well as the arrangement of work and equipment (instrumentation, chemicals, premises, personnels) of the pharmacokinetic laboratory.